Revisiting amlodipine induced pedal edema: a student’s perspective - Nemani, Swathi; Rao, Yeshwanth (International Journal of Basic & Clinical Pharmacology, 2017)
Amlodipine, a dihydropyridine, is used frequently used in the treatment of hypertension and angina pectoris. The drug acts by blocking the L-gated calcium channels which causes the blood vessels to relax. It's taken orally and excreted through the urine like many other drugs. Calcium channel blockers are usually well tolerated but as always exceptions always exist. Common side effects are constipation, dizziness, flushing, and pre-tibial edema. Pre-tibial edema has been a very common side effect that has lead the drug to be withdrawn in some patients therapy.